Ansätze zur lokalen Bayes'schen Fusion von Informationsbeiträgen heterogener Quellen - Sander, Jennifer (Karlsruher Schriften zur Anthropomatik, 2021)
The solution of various tasks benefits from information fusion or even requires it. The Bayesian fusion methodology is clear, well-founded and fulfills the essential requirements for a meaningful methodology also for fusing the contributions of heterogeneous information sources. In many practically relevant tasks, Bayesian methods cause high, often unacceptable effort. In the work, novel approaches to cope with Bayesian fusion in such situations are formulated and investigated.